Os limites das políticas públicas/estatais para o campo hoje e a possibilidade de uma superação - Goldschmidt, Mírian Helena (2016)
What are public / state policies? What is the necessary understanding to think public / state policies for rural education? What is rural? What is urban? What criteria to use to conceptualize what is rural and what is urban? What questions are appropriate for this debate? To answer these questions, this paper aims to study public / state policies and, therefore define what state and its actions to play as such and also submit that rural and urban, far from being just geographical areas are different social content, but are not watertight and not dichotomous, on the contrary, to be able to grasp all of its contents, you must understand their relationship as a complex, as a continuity. The rural and urban reproduce a concrete social reality, are part of the same society. From this idea, thinking the continuity of relations, a complex, between rural and urban, we need to rethink public / state policies developed educational, surpassing the idea of dichotomy, simple separation between these spaces. That is, if they are not watertight spaces that can not be thought of separately, so the public / state policies should be developed articulately. Affirm this need for joint, is not discount that rural and urban have their specificities, but it is understood that these are only felt in full, as are parts of the same society, unlike the Field of Education points. Likewise takes education as public / state policies must be universal and meet the whole of society. literature on the subject and document analysis was conducted from a historical materialist perspective.